Kajian Pembentukan Hukum Internasional di Komite Antariksa Perserikatan Bangsa-Bangsa (PBB) (Lex Jurnalica, 2009)
United Nations Commiteee on Peaceful Uses of Outer Space is the first of United Nations Com-mittee which apply using consensus procedures in adopt its decisions.  The result of the Com-mittee and the both Subcommittee (Scientific and Technical Subcommitee and Legal Subcommitee) use this method in adopting five United Nations Treaties on Outer Space and become positive international space law and  have been ratified by some States.  There are several challenge for the implementing of this method such as having much times to make every decisions.  This paper investigates how to implement this method in making decisions.Keywords:  International Law,  United Nations Commiteee, Peaceful